Impact of climate change on the distribution of Isaria cicadaeMiquel in China: predictions based on the MaxEnt model - He, Zhipeng; Ali, Habib; Wu, Junhao; Liu, Zhiqian; Wei, Xinju; Zhuo, Zhihang (Frontiers in Microbiology, 2025)
IntroductionIsaria cicadae, a historically valued edible and medicinal fungus in China, has been experiencing a critical decline in abundance due to ecological degradation and overexploitation. Understanding its potential distribution is essential for promoting sustainable harvesting practices.MethodsThis study utilizes the MaxEnt model, combined with known distribution records and 22 environmental variables, to predict the potential distribution of I. cicadae under three representative emission scenarios (CMIP6: SSP1-2.6, SSP2-4.5, and SSP5-8.5) for the 2050s and 2070s.ResultsThe analysis identifies seven key environmental variables influencing the habitat suitability of I. cicadae: the mean temperature of the driest quarter (bio09), the mean temperature of the wettest quarter (bio08), precipitation in the wettest month (bio16), the mean diurnal range (bio02), isothermality (bio03), elevation, and slope. Currently, I. cicadae is mainly found in the provinces of Yunnan, Sichuan, Hunan, Hubei, Guizhou, Jiangxi, Guangxi, Fujian, Anhui, and Zhejiang, with Yunnan and Sichuan having the largest areas of high suitability at 25.79 × 104 km2 and 21.36 × 104 km2, respectively.DiscussionJiangxi, Hunan, Yunnan, Guizhou, Fujian, and the Guangxi Zhuang Autonomous Region are identified as primary regions of high suitability. This study aims to further elucidate the impact of the environment on the distribution of I. cicadae from a geographical perspective and provide theoretical insights for the future cultivation and conservation strategies of this species.